Isu-Isu Kebijakan Pendidikan Islam - Meilinda Sari Putri; Qolbi Khoiri (Journal on Education, 2023)
This study is to identify policy issues in Islamic education. In this study, the authors used a qualitative research method with a meta-analysis approach, analyzing data from several previous studies. The results of this analysis indicate that there are several Islamic education policy issues, namely as follows: (1) application of the student-centered approach in Islamic education, (2) Islamic education curriculum, (3) improving the quality of educators, (4) student management, (5) budgeting , (6) Equity distribution and arrangement of the number of teachers in Indonesia and (7) quality of education.